Tackling physical inactivity and inequalities: implementing a whole systems approach to transform community provision for disabled people and people with long-term health conditions - Anna Pettican; Robert Southall-Edwards; Gina Yannitell Reinhardt; Valerie Gladwell; Paul Freeman; William Low; Robert Copeland; Louise Mansfield (BMC, 2024)
Abstract Background Physical inactivity is a global public health priority. There are known health and well-being consequences of being inactive, and the benefits of being physically active are well established. However, there are persistent inequalities when it comes to how physically active people are, with disabled people, people living with long-term health conditions, and people residing in areas of socio-economic deprivation being particularly affected. Methods such as whole system approaches (WSAs), which are dynamic, multifaceted, and engage all relevant stakeholders, have gained momentum as an approach to address such complex public health problems. However, evidence relating to the implementation of WSAs to address physical inactivity is lacking. The aim of the Prevention and Enablement Model (PEM) was to take a whole system approach in Essex to encourage and support disabled people and/or individuals living with long-term health conditions to be more active, happier, and to live more independently. Methods The aim of this study was to explore the enablers, challenges, and reflections associated with the process of designing and implementing the PEM. Semi-structured interviews (n = 12) were used to collect data from people involved in the PEM's design, implementation and/or delivery. Data was analysed using Braun and Clarke's reflexive thematic analysis. Results Four themes were identified: (1) Working collaboratively: Specific enablers of time and space were identified as important in the planning and implementation of a WSA (2) Leadership and planning: Distributed and flexible leadership was identified as central to successful implementation (3) Re-orientating practice: Highlighted the transformative potential of a whole system approach and how it contrasts with conventional work practices, and (4) Reflection and learning: Informing ongoing refinements and further implementation of successful system change. Conclusions These findings highlight the challenge and complexity of implementing a WSA that involves diverse stakeholders from across adult social care, the NHS, and the third sector. Several important enablers are identified, such as leadership and planning, and the challenges and discomfort that can arise whilst changing systems. Ongoing efforts are required to ensure that different elements of the system collaborate effectively to address inequalities in physical activity participation, through the implementation of a WSA.